Role of psychiatric hospitals during a pandemic: introducing the Munich Psychiatric COVID-19 Pandemic Contingency Plan - Kristina Adorjan; Oliver Pogarell; Dorothee Streb; Frank Padberg; Christian Erdmann; Gabriele Koller; Florian Raabe; Daniela Reich-Erkelenz; Sylvia de Jonge; Karin Neumeier; Peter Zill; Karl-Walter Jauch; et al. (BJPsych Open, 2021)
Background Psychiatry is facing major challenges during the current coronavirus disease 2019 (COVID)-19 pandemic. These challenges involve its actual and perceived role within the medical system, in particular how psychiatric hospitals can maintain their core mission of attending to people with mental illness while at the same time providing relief to overstretched general medicine services. Although psychiatric disorders comprise the leading cause of the global burden of disease, mental healthcare has been deemphasised in the wake of the onslaught of the pandemic: to make room for emergency care, psychiatric wards have been downsized, clinics closed, psychiatric support systems discontinued and so on. To deal with this pressing issue, we developed a pandemic contingency plan with the aim to contain, decelerate and, preferably, avoid transmission of COVID-19 and to enable and maintain medical healthcare for patients with mental disorders.